Numerical studies of turbulent wall-jets for mixing and combustion applications - Ahlman, Daniel (KTH, Mekanik, 2007)
Direct numerical simulation is used to study turbulent plane wall-jets. The investigation is aimed at studying dynamics, mixing and reactions in wall bounded flows. The produced mixing statistics can be used to evaluate and develop models for mixing and combustion. An aim has also been to develop a simulation method that can be extended to simulate realistic combustion including significant heat release. The numerical code used in the simulations employs a high order compact finite difference scheme for spatial integration, and a low-storage Runge-Kutta method for the temporal integration. In the simulations the inlet based Reynolds and Mach numbers of the wall-jet are Re = 2000 and M=0.5 respectively, and above the jet a constant coflow of 10% of the inlet jet velocity is applied. The development of an isothermal wall-jet including passive scalar mixing is studied and the characteristics of the wall-jet are compared to observations of other canonical shear flows. In the near-wall region the jet resembles a zero pressure gradient boundary layer, while in the outer layer it resembles a plane jet. The scalar fluxes in the streamwise and wall-normal direction are of comparable magnitude. In order to study effects of density differences, two non-isothermal wall-jets are simulated and compared to the isothermal jet results. In the non-isothermal cases the jet is either warm and propagating in a cold surrounding or vice versa. The turbulence structures and the range of scales are affected by the density variation. The warm jet contains the largest range of scales and the cold the smallest. The differences can be explained by the varying friction Reynolds number. Conventional wall scaling fails due to the varying density. An improved collapse in the inner layer can be achieved by applying a semi-local scaling. The turbulent Schmidt and Prandtl number vary significantly only in the near-wall layer and in a small region below the jet center. A wall-jet including a single reaction between a fuel and an oxidizer is also simulated. The reactants are injected separately at the inlet and the reaction time scale is of the same order as the convection time scale and independent of the temperature. The reaction occurs in thin reaction zones convoluted by high intensity velocity fluctuations. === QC 20100621